CHANGE OF PHOSPHORUM AND EXCHANGE SODIUM CONDITIONS OF CHESTNESS SOILS UNDER THE INFLUENCE OF GRAZING - Nasiyev B.N.; Manolov I.G.; Bekkaliyev A.K. (Scientific Journal of Pedagogy and Economics, 2020)
In order to prevent adverse anthropogenic effects on pastures in modern agricultural agriculture, an adaptive strategy for further increasing food production and agricultural raw materials must be based on the principles of environmental management, which includes a number of activities, the most important of which are seasonality of pasture release taking into account the state of vegetation cover and its yield; determination of optimal livestock load per unit area. The research aim is agrochemical assessment of grazing land cover depending on grazing technology. As a result of the carried out studies, the negative influence of intensive grazing of farm animals on the content of mobile forms of phosphorus and exchanged sodium chestnut types of pasture soils of West Kazakhstan region was found. As a result of excessive grazing, the content of moving phosphorus of chestnut soils decreased, the content of exchange sodium increased as part of exchange bases and non-salt soils became a medium degree of salt content. The results of the studies confirmed the existence of a statistical pattern of reduction of mobile phosphorus content and increase of exchange sodium content as grazing intensity increases across all soil types